Optimization, Preparation, and Cytotoxic Potential of Pyrus communis Extract Loaded Ethosomes on Skin Cancer Cell Lines - Kangra, Kiran; Garg, Vandana; Dhiman, Anju; Dutt, Rohit (Current Topics in Medicinal Chemistry, 2025)
<span class=
Keywords: P. communis